Real Time Monitoring in Disasters. (21st March 2013) - Scott, Nigel; Batchelor, Simon
Abstract This article discusses some of the opportunities emerging from the changing Information and Communication Technology (ICT) landscape for improving and enhancing agency response within the disaster cycle. There are constant calls for better coordination among agencies, of engaging with the community to improve resilience, of better governance, of community empowerment. Any action in a system affected by disaster will be guided by a complex mix of human response, socioeconomic context, political and power factors, and technology. The technology is only one component in a complex environment. Nevertheless, as this article outlines, recent shifts in the ICT landscape have not only created opportunities for more and timely data, they have opened the way for new ways of working. They have the potential to increase interagency cooperation, they have the potential to deliver community engagement, breaking free from extraction of information to a co‐construction of data, and they even have the potential to empower citizens and to enable better governance.